1996
DOI: 10.1177/019394599601800406
|View full text |Cite
|
Sign up to set email alerts
|

Illness Experiences and Health Recovery Behaviors of Patients in Southern Appalachia

Abstract: The purpose of this exploratory study was to gain a better understanding of the influences of Appalachian culture and rural living on illness experiences and health recovery behaviors. The study sample consisted of 257 randomly selected adult patients admitted to medical-surgical units in eight hospitals in West Virginia. Patients completed interviews in the hospital and by phone and in their homes 1 month after hospital discharge. In addition, 203 nurses and 79 physicians completed a values survey and decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…2003). A study framed by the Cox model showed that patients who perceived their health status as moderately to seriously ill on hospitalization expressed satisfaction with the hospital experience in follow‐up interviews 2 weeks after discharge (Russwurm et al. 1996).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2003). A study framed by the Cox model showed that patients who perceived their health status as moderately to seriously ill on hospitalization expressed satisfaction with the hospital experience in follow‐up interviews 2 weeks after discharge (Russwurm et al. 1996).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, patients with better self-perceived health status at admission have reported higher satisfaction with care (Thi et al 2002, Cleary et al 2003. A study framed by the Cox model showed that patients who perceived their health status as moderately to seriously ill on hospitalization expressed satisfaction with the hospital experience in followup interviews 2 weeks after discharge (Russwurm et al 1996).…”
Section: Patients' Personal Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Denham's study of Appalachian families in Ohio 14 and Cavender's observation of Appalachian families in Tennessee 24 also documented this maternal role as the arbiter of the family's health‐related concerns. A study of hospitalized adults in West Virginia found that women maintained the traditional role of nurturer and that family, health, and salvation were the most important values for patients in the study 25 . Horton observed that Appalachian women serve as spokespersons for their families 26 .…”
mentioning
confidence: 99%
“…The vast majority of families in the region maintain a membership in a church and well over one third of residents indicate that they attend church at least once per week 25. Additionally, recent evidence refutes the assumption that religious communities promote negative constructs like fatalism or lack of self-efficacy 26. For the past 2 decades, faith communities have been selected as a primary setting and/or partner for the delivery of health educational messages and interventions, most especially in African American faith organizations 27,28…”
Section: Community Assets Underlying the Intervention: Appalachian Church/faith-placed Interventions And Social Network/lha Interventionsmentioning
confidence: 99%